Intradermal Tuberculin Test in Water Buffalo (Bubalus bubalis): Experimental use of Mycobacterial Antigens for the Diagnosis of Bovine Tuberculosis - Martucciello, Alessandra; Mazzone, Piera; Napolitano, Francesco; Bezos, Javier; Grandoni, Francesco; Boniotti, Maria Beatrice; Cagiola, Monica; Cappelli, Giovanna; Di Vuolo, Gabriele; Galiero, Giorgio; Signorelli, Federica; De Carlo, Esterina (Journal of Buffalo Science, 2024)
The study aims to evaluate the potential use of mycobacterial ESAT6 and CFP10 antigens, Early Secretory Proteins (ESP) in the Skin Test used for bovine tuberculosis (TB) diagnosis in Water Buffalo. A pilot study was performed on 21 buffaloes from a TB outbreak and 11 buffaloes from a TB-free herd. Three concentrations of ESAT6-CFP10 (10, 20, and 30 mg) and two of ESP (50 and 100 µg) were inoculated in the Skin Test, along with PPDB, PPDA, and PBS as a negative control. Skin thickness was measured with calipers before the test and every 24 hours for 4 days. Then, to evaluate the specificity of the antigens, a field study was conducted, and 100 buffaloes from a TB-free herd were inoculated using the best antigens concentration derived from the pilot study. In the positive buffaloes, the strongest skin response was to PPDB at 24h, with some subjects becoming inconclusive at 72 and 96 h. A peak response to PPDA at 48 hours was detected, followed by a slight decrease. The response to ESP-100 µg remained high at 24 and 48 h, then decreased, remaining positive at 72 h. In the 100 TB-free buffaloes, the best specificity was observed using ESAT6-CFP10 and ESP. ESP yielded the best results, showing higher reactivity in infected animals and no reactivity in the healthy ones at 72 h. Therefore, ESP could be an excellent candidate for further extensive studies in the buffalo species to improve Skin Test performance.